Self-censorship: the most insidious gag - Peter Cronau (Asia Pacific Network, 1995)
Journalists feel the pressures to conform to the accepted values of their workplace. But those values come not just from editors and producers above them, but significantly from the journalists' peers—their fellow journalists.